2022
DOI: 10.1111/andr.13179
|View full text |Cite
|
Sign up to set email alerts
|

Sperm‐oviduct interactions: Key factors for sperm survival and maintenance of sperm fertilizing capacity

Abstract: Background: Although millions or even billions of sperm are deposited in the female genital tract, only very few sperm reach the oocyte, and only one single spermatozoon will successfully fertilize. During the journey of the sperm within the female genital tract, the interactions between spermatozoa and fallopian tube are critical for sperm selection, sperm survival, and maintenance of sperm fertilizing capacity.Results: This review will provide a comprehensive overview of the latest findings regarding sperm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 83 publications
(154 reference statements)
0
11
0
Order By: Relevance
“…In the same study, transmission electron microscopy of the OECs after sperm incubation revealed an active endoplasmic reticulum in ciliated and secretory oviduct cells, which suggests an increase in protein synthesis and trafficking [98]. As discussed by Kölle [99], the oviduct may also respond to sperm interaction with the secretion of nutrients that would support sperm viability.…”
Section: Boar Ex Vivo Oviduct Explantmentioning
confidence: 63%
“…In the same study, transmission electron microscopy of the OECs after sperm incubation revealed an active endoplasmic reticulum in ciliated and secretory oviduct cells, which suggests an increase in protein synthesis and trafficking [98]. As discussed by Kölle [99], the oviduct may also respond to sperm interaction with the secretion of nutrients that would support sperm viability.…”
Section: Boar Ex Vivo Oviduct Explantmentioning
confidence: 63%
“…The term contralateral refers to the oviduct that is on the opposite side of the reproductive tract to ovulation/COD. The ampulla was selected for investigation because this part of the oviduct is the site of sperm binding, fertilization and the first embryo-maternal communication (Kölle et al, 2009(Kölle et al, , 2020Kölle, 2022).…”
Section: Oviduct Samplingmentioning
confidence: 99%
“…Overall, the percentage of motile, immotile, and hyperactivated sperm did not significantly differ in ampullae from cows with FC and LC (p = 0.14, two-way ANOVA with Tukey's multiple comparisons test) (Figure 9e). This study is the first to elucidate the impact of COD on the microarchitecture and function of the oviduct, which is the site of formation of the sperm reservoir, fertilization and early embryonic development and plays a key role in fertility (Kölle et al, 2009(Kölle et al, , 2020Kölle, 2022). Our previous studies (Scully et al, 2021) have already shown that COD impacts the transport function of the oviduct, highlighting the importance of investigating the effects of COD on all reproductive organs in addition to the existing studies of the ovarian anatomical features associated with COD and its effects on ovarian function (Borş & Borş, 2020;Gareis et al, 2023).…”
Section: Cod Alters the Synthesis Of Acidic Mucopolysaccharides In Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Before ejaculation, sperm are stored in a quiescent state within the cauda epididymis (De Jonge, 2005). Once deposited into the female genital tract, sperm undergo a series of biochemical and physiological changes, known as capacitation, that lead to their acquisition of fertilizing competency (De Jonge, 2017; Kölle, 2022; Puga Molina et al, 2018). Increases in extracellular Ca 2+ , HCO 3 − , and albumin initiate a signaling cascade that results in the production of cAMP, activation of protein kinases, and protein phosphorylation (Krapf et al, 2010; Puga Molina et al, 2018; Visconti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%